2011
DOI: 10.1021/jp201916z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Ni- and Co-Substituted ZnO Nanoparticles: Synthesis, Optical, and Magnetic Properties

Abstract: International audienceNi- and Co-substituted ZnO nanoparticles were synthesized using forced hydrolysis of acetate metallic salts in a polyol medium. The X-ray diffraction patterns show a hexagonal wurtzite structure (space group P63mc). The characteristic absorption bands of UV-vis-IR spectra are correlated with the d-d transitions of tetrahedrally coordinated Co2+ and Ni2+ ions in octahedral and tetrahedral sites. The photoluminescence spectra exhibited a typical ZnO UV-exitonic emission band around 380 nm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 50 publications
(63 reference statements)
1
33
1
Order By: Relevance
“…Mn, Fe, Co, Ni) doped ZnO materials. Nickel doped ZnO diluted magnetic semiconductor with room temperature ferromagnetism in the form of thin films and nanocrystals has been studied [11][12][13][14]. Different methods such as thermal decomposition, sol-gel, hydrothermal and solvothermal method etc., have been used to synthesize the ZnO nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Mn, Fe, Co, Ni) doped ZnO materials. Nickel doped ZnO diluted magnetic semiconductor with room temperature ferromagnetism in the form of thin films and nanocrystals has been studied [11][12][13][14]. Different methods such as thermal decomposition, sol-gel, hydrothermal and solvothermal method etc., have been used to synthesize the ZnO nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Doping ZnO nanoparticles with magnetic elements was suggested to obtain new binary probes with both fluorescent and magnetic functions, so that the labeled tissues deep within the animal body could be detected by MRI techniques. However, many ZnO nanoparticles doped with conventional magnetic elements, such as Fe, Co, Ni, and Mn, showed almost no luminescence in the visible region 37–42. One reason is that doping nanocrystals usually requires high temperature treatment, but under such conditions the defect concentration in ZnO nanoparticles will decrease and the defect‐related visible emission will be weakened.…”
Section: Zno Nanoparticles For Bioimagingmentioning
confidence: 99%
“…Dietl et al reported ferromagnetism at room temperatue (RT-FM) for diluted magnetic semiconducting compounds, such as 3d ions M 2 +-substituted zinc oxide [2]. This class of materials is potentially interesting for spintronic devices, such as spin valves, magnetic sensors, spin light-emitting diodes, and non volatile memory [3]. Intrinsic Co-doped ZnO should be paramagnetic but room temperature ferromagnetism (RTFM)…”
Section: [N Troductionmentioning
confidence: 99%